On-chip read-out of picomechanical motion under ambient conditions. Issue 5 (22nd December 2014) - Putrino, Gino; Martyniuk, Mariusz; Keating, Adrian; Faraone, Lorenzo; Dell, John
Abstract : A novel method for monitoring the nanomechanical movement of suspended cantilever structures which has great potential for use in applications ranging from biological/chemical sensing to atomic force microscopy. Abstract : Monitoring the nanomechanical movement of suspended cantilever structures has found use in applications ranging from biological/chemical sensing to atomic force microscopy. Interrogating these sensors relies on the ability to accurately determine the sub-nanometre movements of the cantilever. Here we investigate a technique based on the combination of integrated silicon photonics and microelectromechanical systems (MEMS) to create an optically resonant microcavity and demonstrate its use for monitoring of the position of cantilevers on the picometer scale under ambient conditions with dynamic range extending over several microns. The technique is interferometric, and we show it to be sufficiently sensitive to measure both the first and second modes of cantilever Brownian motion. We anticipate that application of this technique will provide a physically robust, picometer precision, integrated cantilever movement read-out technology which can take cantilever sensors from laboratory controlled environments into real world conditions, allowing everyday applications.